Old-Lithuanian irrealis in Chylinskis’ Bible - Brudzyński, Paweł (Baltistica, 2020)
The paper deals with the conditional in the Old Lithuanian text of Samuel Boguslaus Chylinskis’ Bible translation. Attention is drawn to the differences between the language of Chylinskis’ versions of the Old Testament, which was printed, and the New Testament, which remained in the manuscript. The paper discusses the differences in the forms of the irrealis between the Old and New Testaments translations and the role of editorial interference as a source of these differences. Apart from this, the article gives an overview of the uses of the irrealis in the Chylinskis’ Bible.